Aerosol vertical profile retrieved from ground-based MAX-DOAS observation and characteristic distribution during wintertime in Shanghai, China. (November 2018) - Zhang, Jiawei; Wang, Shanshan; Guo, Yanlin; Zhang, Ruifeng; Qin, Xiaofei; Huang, Kan; Wang, Dongfang; Fu, Qingyan; Wang, Jie; Zhou, Bin
Abstract: Multi-AXis-Differential Optical Absorption Spectroscopy (MAX-DOAS) measurements were performed to remote sensing the aerosol vertical profiles in suburb area of Shanghai, China from April to December 2017. The retrieval of aerosol extinction was based on the optimal estimation method combing the measured oxygen dimer O4 absorption with simulation of forward radiative transfer model. It suggests that the employment of O4 correction factor (CFO4 ) for daily aerosol retrieval should be adjusted, which includes three typical cases that a fixed CFO4, no usage of CFO4 and different CFO4 in the morning and afternoon. In cases of using CFO4, elevation angle dependent CF O 4 ( α ) were further proposed. Moreover, the retrieval results can be improved if the local sounding data of atmospheric temperature and pressure profiles were introduced into the forward radiative transfer model without utilizing additional CFO4 . Afterwards, the retrieved Aerosol Optical Depth (AOD) and the surface Aerosol Extinction Coefficient (AEC) was in a good agreement with the AOD obtained from sun photometer observations and in-suit PM2.5 concentrations, with a correlation coefficient R of 0.866 and 0.833, respectively. Besides, the vertical AEC profiles retrieved by MAX-DOAS were also validated well by the co-located lidar measurement. It can be found that the particles were mainly distributed below 1 km, and the maximum AEC usually appeared in the lowest 300 m and decreased with the altitudes. The averaged AEC within 1 km varied from 0.20 to 0.75 km −1, 0.25 to 1.08 km −1, 0.55 to 2.45 km −1 and 0.70 to 2.75 km −1 under different air quality of Grade II, III, IV and V. The sounding meteorological parameters and backward trajectories of air masses were integrated to diagnose the influencing factor of AEC at different altitudes, which illustrated that the AEC levels at lowest layer were impacted by the long distance transportation of air pollutants from north-northwest and regional local air pollution nearby during the winter time. The study shows that ground-based MAX-DOAS observation is powerful remote sensing technique to provide better understanding of aerosol properties at both ground surface and higher altitudes. Highlights: Aerosol vertical distribution were obtained by MAX-DOAS measurements in Shanghai. O4 correction factor (CFO4 ) need to be adjusted in the aerosol retrieval scheme. Using local temperature and pressure profiles can improve the aerosol retrieval. MAX-DOAS remote sensing are well validated by other auxiliary datasets. High aerosol extinction usually occurred at the lowest layer below 0.3 km in winter.